Prediction of deterioration and mean service life of different roofing systems of DepEd school buildings using a discrete Markov chain - Paniorotan, Mohamad Said Bren M.; Acosta, Timothy John S. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The roof is the most vulnerable building envelope because of its constant exposure to natural hazards such as wind, rain and extreme heat. The performance of a roof system deteriorates with time due to aging effects, various environmental degradation factors, poor workmanship and maintenance. It is important to monitor these deteriorations because of the risk of damage to the roof itself and the contents below it. This information on the deterioration can be used to plan for an effective maintenance operation, which in effect will prolong the life of the roof system and prevent future damage. The study was conducted in Region VIII and IX wherein the data were obtained from the maintenance records of the Physical Facilities and Operations Unit of the respective DepEd offices. Based on the empirical data, a discrete Markov chain is developed to predict the deterioration and mean service life of the roof system of one storey DepEd school buildings. A discrete Markov chain is the model used in this study because it is able to capture the random nature of the performance of the roofing systems. The model makes use of a seven-integer rating as a quantitative measure of the performance of roofing system and a one-year interval transition probability matrix developed from historical data of the maintenance of DepEd school buildings. A Weibull distribution is used to fit the average deterioration curve. From the average deterioration curve of some type of DepEd school building, the mean service life of the roofing system is determined. The transition probability matrices are used to predict the probability of failure of the roofing systems. From the results of this study, the mean service life of the roofing systems is better than the standard mean service life set by DepEd for their school buildings. The standard mean service life of the DepEd school buildings as set by DepEd is 25 years, regardless of the type, design and materials used. The mean service life of BLSB type 1, BLSB type 2, BLSB type 3 and Marcos Type are 41, 39, 35 and 47 years respectively. Based on these values, the Marcos type has the strongest roofing system. This may be attributed to the variation of the materials used between the types. Marcos type for instance, has light steel roof frames while the BLSB's has timber roof frames.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Roofing; School buildings -- Philippines